Impacto da saúde oral e fatores sociodemográficos na qualidade de vida da população idosa - Dallasta, Thaís Cauduro (2016)
Introduction: The quality of life related to oral health is a multidimensional concept that includes the subjective evaluation of the oral health of the individual, functional aspects, general well-being, emotional well-being, expectations and satisfaction with their self-care. Furthermore, it is part of the general state of health and wellness. This paer is to assess the impact of oral health and sociodemographic factors in life quality of elderly people. Methods: A cross-sectional survey with elderly participants in a social group in Santa Maria, RS state, was performed. Data were collected in the same living group by previously trained interviewers. It was used for data collection, the instrument Oral Health Impact Profile (OHIP -14), and a structured interview addressing sociodemographic and health issues. Data were analyzed using STATA 13.0 (Stata 13.0 for Windows; Stata Corporation, College Station, TX, USA). The descriptive analysis provided the statistics of clinical and sociodemographic characteristics as well as the average values of OHIP-14 scores and their respective domains. The differences between the mean scores of OHIP-14 according to the clinical and sociodemographic variables were statistically compared using the Mann- Whitney test, adopting a significance level of 5%. The conducted study design was approved by the Ethics Committee of the Federal University of Santa Maria and all participants signed a term of consent form. Results: A total of 64 subjects were analyzed. The average age was 69.8 years, ranging from 60 to 88 years. BMI ranged from 17.99 to 42.64 kg/m (average of 28.28 ± 5.05 kg/m²), and 53, 13% (34/64) had normal weight, 15.62% (10/64) low weight and 31.25% (20/64) had obesity according to BMI classification. The mean weight was 68.7 kg ranging from 46.3 kg to 107.9 kg. The highest average of the total scores of OHIP-14 was observed in subjects who had low education (<5 years), low income (≤ R $ 2,500), altered taste, difficulty in feeling the taste of food, which were depressed and malnourished. Schooling also associated with OHIP-14 scores in the psychological discomfort and disability fields, just as changes in taste also influenced the areas of functional limitation and disability. Individuals malnourished worsened their quality of life when compared to individuals with excess weight in the total scores and disability domain. Conclusion: Oral disorders associated with worse quality of life were found in elderly women who had low family income, low education and those who had a worse nutritional diagnosis.